WHY SCIENTIFIC RESEARCH OF A LECTURER IS THE «LAME HORSE» OF MODERN SCIENCE? - Maria A. Belyaeva (Образование и наука)
The aim of the article is to represent reflections on the crisis of science and logical thinking (within the framework of Social Science, Humanities and higher education) that has its local and global manifestations; the author focused own attention on the manifestations in order to understand its depth and possible ways of overcoming them. Methods. A number of theoretical methods have been used in the article: analysis and synthesis, induction and deduction, comparison and classification, methods of extrapolation and modeling, as well as participant observation. Results. Local manifestations of the crisis of science and logical thinking associated with human factor in the national system of higher professional education in the era of virtualization and commercialization are expressed in reducing efforts and productivity of scientific research, due to the existing contradictions between changed requirements that enumerate professional duties of a lecturer and possibilities of combining and productive implementation of traditional and new professional roles. In particular, researches turn to promoters of themselves to solve financial and organizational issues of a scientific research and promotion of ratings. Changes in the sense of scientific activity in respect to educators and their personal attitude to new requirements will eventually face the eternal problem of attitude to knowledge and to the actual problem of change of knowledge subject in non-classical model and post-non-classical model of science. Expression of a researcher’s individuality encounters many obstacles (the author has identified 10 of them) and is complicated by new facets of this subjectivity, induced by «logistics turn point» in science. Scientific novelty. The author proves that it is necessary to change nonclassical subject knowledge model (where the corporate subject leaning for the general ways and collective norms of scientific activity dominates) for postnonclassical – individualized, wherein the subject possesses own way of thinking, own language; as it allows to create new knowledge. However, occurrence of such researcher is complicated by many obstacles. The author introduces the concept of «scientific logistics», i.e. scientific advancement of research results in virtual and real-life spaces in order to gain a dividend in material or symbolic form. When scientific logistics from a subsidiary position is moved to the center of academic life «logistics turn point» in science occurs. The meaning of learning is changing. Now it is more about search of potential consumers of the information then search of the truth. Scientific logistics measured in scientometric quantitative indexes and in their income as a calculated direct commercial effect performs the image function for a research, providing improved individual and corporate status. At the same time, these changes can turn into the veiled substitution of true scientific creativity, its transformation into formal manufacture of «a pseudoscientific spam». Practical significance. The research implementations can be useful for conceptual foresight of possible ways of improving scientific research at university, including possibility of making a new working agreement – «and effective contract», grounding its alleged advantages and objective limits on the way of increasing efforts and productivity of scientific research.